Analysis of the Development of WeChat Mini Program - Hao, Lei; Wan, Fucheng; Ma, Ning; Wang, Yicheng (Journal of physics. Conference series, 2018)
In 2017, we called it "WeChat Mini Program and the first year". Since then, the development of the WeChat Mini Program has been booming. At present, the next generation of mobile Internet industry is developing toward the development of "micro, light, and small", like the WeChat Mini Program, this revolutionary lightweight "APP" that does not require downloading, runs out, and simultaneously has information publishing, advertising, and service functions, will become the best choice to replace the mobile client APP. This article will analyze the system implementation and prospects of the WeChat Mini Program, and study the system architecture, key technologies and market prospects based on the WeChat "small program" development.